Antiviral chemotherapy facilitates control of poxvirus infections through inhibition of cellular signal transduction - Yang, Hailin; Kim, Sung-Kwon; Kim, Mikyung; Reche, Pedro A.; Morehead, Tiara J.; Damon, Inger K.; Welsh, Raymond M.; Reinherz, Ellis L. (The Journal of Clinical Investigation, 2005)
The EGF-like domain of smallpox growth factor (SPGF) targets human ErbB-1, inducing tyrosine phosphorylation of certain host cellular substrates via activation of the receptor’s kinase domain and thereby facilitating viral replication. Given these findings, low molecular weight organic inhibitors of ErbB-1 kinases might function as antiviral agents against smallpox. Here we show that CI-1033 and related 4-anilinoquinazolines inhibit SPGF-induced human cellular DNA synthesis, protein tyrosine kinase activation, and c-Cbl association with ErbB-1 and resultant internalization. Infection of monkey kidney BSC-40 and VERO-E6 cells in vitro by variola strain Solaimen is blocked by CI-1033, primarily at the level of secondary viral spreading. In an in vivo lethal vaccinia virus pneumonia model, CI-1033 alone promotes survival of animals, augments systemic T cell immunity and, in conjunction with a single dose of anti-L1R intracellular mature virus particle-specific mAb, fosters virtually complete viral clearance of the lungs of infected mice by the eighth day after infection. Collectively, these findings show that chemical inhibitors of host-signaling pathways exploited by viral pathogens may represent potent antiviral therapies.